Macromedia® Fireworks® 8 : Training from the Source - Schulze, Patti (Adobe Press, 2005)
If you learn best by doing, and what you're intent on doing is create stunning Web graphics with Macromedia Fireworks 8, this is the place to turn. The best-selling tutorial book on Fireworks has been completely updated to get you hands-on fast with all of the program's most important features, including its newest: additional blend modes, support for special characters and AutoShape properties, workflow improvements, and more. Through project-based lessons that equal 16 to 20 hours of instruction, you'll cover the entire process of creating Web graphics with Fireworks 8-from creating images to optimizing and exporting them. Simple step-by-step instructions, loads of screen shots, and a CD with media files and a trial version of the program will have you creating rollovers, pop-ups, and more in no time. Whether you're new to the world of Fireworks graphics or a veteran user eager to tap the power of the latest version, you'll find the trusted, Macromedia-certified instruction you need in these pages.